HLA-DR antigens in systemic lupus erythematosus: association with specificity of autoantibody responses to nuclear antigens. Issue 6 (June 1987) - Smolen, J S; Klippel, J H; Penner, E; Reichlin, M; Steinberg, A D; Chused, T M; Scherak, O; Graninger, W; Hartter, E; Zielinski, C C
Abstract : HLA-DR antigens and autoantibodies to the nuclear or cytoplasmic antigens Ro/SSA, La/SSB, Sm, and RNP were determined in North American and Austrian patients with systemic lupus erythematosus (SLE). Analysis of the association of antibodies to these ribonucleic acid (RNA)-protein antigens with HLA-DR antigens showed that HLA-DR3 was related to the presence of anti-Ro/SSA or anti-La/SSB, or both. In contrast, anti-Sm or anti-RNP, or both were associated with HLA-DR4. HLA-DR5 was associated with absence of these autoantibodies. The data extend evidence for the complexity and heterogeneity of SLE. Moreover, they indicate that, in SLE, genes linked to those coding for HLA-DR antigens, are related to the specificity of autoantibody responses rather than to the primary immunological abnormalities of this disorder.